Young Learner’s Incidental Language Learning of English Speaking Skill (A Case Study) - Gumilar Eka Ramadhan; Aa Qonaatun; Ida Nuraida (English Education, Linguistics, and Literature Journal, 2022)
Abstract: The objective of this research was to find out the process young learners incidental language learning of English speaking skill. This research is used a case study. The population of this research was the young learners. The subjects of this research were chosen by using the Interview, Documentation, and Observation technique. The data were collected using observation, interview, and documentation techniques. The technique of data is by WhatsApp media to complete the research. The results of this study show that: (1) young learner's incidental language learning of English speaking skill; (2) young learner's repetition of English speaking skill; (3) and young learner's problem of English speaking skill (3) The result are: (a) The young learners incidental language learning using media English movies and Ablo application for learn English, (b) The young learners repetition language learning using media Youtube and English music for learn English, (c) The young learners problem language learning is the difficulty of getting friends to discuss in English directly to practice English skills.